The Discourse on Innovation in Public Administration and its Adoption in Ibero-America: an Analysis of the CLAD Conventions - Isaza Espinosa, Carolina (Revista del CLAD Reforma y Democracia, 2020)
This paper presents the results of an investigation on the relatively new discourse on innovation in public administration, its origin, meaning, and its use in Ibero-American countries. A discourse analysis of the academic literature and of the use of this concept in the CLAD conventions in an eight year period is conducted. It is evident that the use of the public innovation concept has increased and that it has been adopted by the Ibero-American community represented in CLAD. The implications of the particular uses that this community has given to the concept are also exposed.
Keywords: Administrative Innovation; Public Administration; Public Sector; Administrative Analysis; Latin America; Spain; Portugal